Disease burden and trends of malignant neoplasm of bone and articular cartilage in childhood in China, 1990–2021 and comparison with United States and India: findings from the Global Burden of Disease Study 2021 - Ruibo Li; Xingyue Yuan (Frontiers in Public Health, 2025)
ObjectivesThis study aims to analyze the disease burden and trends of malignant neoplasm of bone and articular cartilage (MNBAC) in Chinese children from 1990 to 2021 using data from GBD 2021, and to compare them with the United States and India.MethodsData on incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for MNBAC in children aged 0–14 years were extracted from GBD 2021. The joinpoint regression analysis model was employed to assess temporal trends, and the average annual percent change (AAPC) was calculated to summarize the trends over the study period.ResultsGlobally, the number of incident childhood cases of MNBAC increased from 9,827 in 1990 to 12,294 in 2021, with an AAPC of 0.38. Similarly, the prevalence of the disease also increased, with an AAPC of 0.39. However, the mortality rate and DALYs rate showed a slight decline, with an AAPC of −0.16 and −0.16 respectively. At the national level, the United States had the highest incidence and prevalence rates, while India had the highest number of incident cases and DALYs. China showed the largest increase in prevalence, with an AAPC of 1.88. India also demonstrated the most significant decline in mortality and DALYs rates. Additionally, the mortality rate and DALYs rate were slightly higher for male children compared to female patients.ConclusionMalignant bone and articular cartilage tumors in children remain a significant public health challenge globally. By strengthening monitoring, increasing investment in medical resources, promoting early screening and intervention, and enhancing international cooperation and exchange, we hope to further reduce the burden of childhood bone cancer and improve children's quality of life and health standards.